COMPARATIVE ASSESSMENT OF LIPID PROFILE IN PRE-MENOPAUSAL AND MENOPAUSAL WOMEN IN NNEWI NIGERIA - P.O., Manafa; N.C., Aguiyi; C.C, Onyenekwe; G.O., Chukwuma; C.O., Okeke; A.C., Ihim; L.O., Okor; C.C., Manafa (European Scientific Journal, ESJ, 2015)
The study was aimed at determining the effect of menopause on lipid profile. A total of 100 apparently healthy subjects who comprised 50 menopausal women aged 45 – 77 years and 50 pre-menopausal women between the aged between 20-52 years were recruited. Ethical approval was obtained from the Faculty of Health Science and Technology, Nnamdi Azikiwe University ethics committee and informed consent of each participant was obtained prior to recruitment. We estimated serum levels of total cholesterol using the enzymatic end point method as described by Roeschlau et al., (1974), HDL was performed using the combination of phosphotungstate precipitation and enzymatic method as described by Burstein et al., (1980), LDL by the combination of polyvinyl sulphate precipitation and enzymatic method of Assman et al., (1984), VLDL was estimated using the method as described by Friedwald et al., (1972) and triglycerides by the enzymatic method as described by Tietz (1990). The results shows that the mean levels of serum triglycerides (TG) and low density lipoprotein cholesterol (LDL cholesterol) showed a statistically significant increase in menopausal women compared with the premenopausal subjects (P<0.05) while there was no significant difference in the mean values of serum high density lipoprotein cholesterol (HDL cholesterol), very low density lipoprotein cholesterol (VLDL cholesterol) and total cholesterol (P>0.05). There was a progressive increase in the mean levels of total cholesterol, triglycerides, LDL-cholesterol and VLDLcholesterol with duration of menopause while the levels of HDL-cholesterol decreased with duration of menopause. There were no significant variations among the various age categories of the menopausal subjects and the levels of the lipid parameters studied (p>0.05). The findings suggest that premenopausal women have less proatherogenic lipid profile than their menopausal counterparts.